Employee Productivity in the Flexible Work Era: An Analysis of the Influence of Work-Life Balance on Individual Performance - Sugito Sugito; Aryani Sairun; Anto Tulim; Rayu Sri Wahyuni; Purnaya Sari Tarigan; Pioner Pelawi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The increasing adoption of flexible work arrangements has highlighted the importance of maintaining a balance between employees' professional and personal lives to enhance organizational performance. This study aims to examine the effect of Work-Life Balance on Individual Performance, with Employee Productivity serving as a mediating variable. A quantitative explanatory research design was employed using a census sampling technique involving 60 employees. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings reveal that Work-Life Balance has a positive and significant effect on Employee Productivity (β = 0.652; p < 0.001), Employee Productivity has a positive and significant effect on Individual Performance (β = 0.598; p < 0.001), and Work-Life Balance also has a direct positive and significant effect on Individual Performance (β = 0.417; p < 0.001). Furthermore, Employee Productivity partially mediates the relationship between Work-Life Balance and Individual Performance (β = 0.390; p < 0.001). These findings indicate that improving employees' work-life balance can enhance both productivity and individual performance, directly and indirectly through increased productivity. Therefore, organizations should implement policies that promote work-life balance to improve employee performance and support sustainable organizational success.